2018
DOI: 10.1093/gbe/evy002
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Proteins of the RNA Interference System in the Arbuscular Mycorrhizal Fungus Rhizoglomus irregulare Provide New Insight into the Evolutionary History of Glomeromycota

Abstract: Horizontal gene transfer (HGT) is an important mechanism in the evolution of many living organisms particularly in Prokaryotes where genes are frequently dispersed between taxa. Although, HGT has been reported in Eukaryotes, its accumulative effect and its frequency has been questioned. Arbuscular mycorrhizal fungi (AMF) are an early diverged fungal lineage belonging to phylum Glomeromycota, whose phylogenetic position is still under debate. The history of AMF and land plant symbiosis dates back to at least 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…Of these, HGT of ribonuclease III was also reported recently in R . irregularis (Lee et al ., ). Most HGT genes were expressed in both fungal spores and extraradical hyphae, and some of them seem to be highly expressed in the spores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, HGT of ribonuclease III was also reported recently in R . irregularis (Lee et al ., ). Most HGT genes were expressed in both fungal spores and extraradical hyphae, and some of them seem to be highly expressed in the spores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glomeromycota, also called arbuscular mycorrhizal fungi, are typical fungal symbionts colonizing the roots of vascular plants and widely-spread on land. 27 Recently, the phylum Glomeromycota has been also detected in marine environments, including Arctic, marine sediments, 3 and hydrothermal ecosystems. 28 And it was not detected in the Mariana Trench in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the RdRp, we found six proteins in G. margarita, more than the one to five generally possessed by non-AMF (Chang et al, 2012;Chen et al, 2015). In our previous work we reported 21 RdRp in R. irregularis, although Lee et al (2018), using more stringent annotation criteria, only reported three.…”
Section: The Comparative Analysis Of Fungal Rnai-related Proteins Revmentioning
confidence: 69%
“…Recent surveys of two AMF genomes allowed a first characterization of the RNAi components (DCL, AGO-like, and RdRp) in this group of obligate biotrophs (Lee et al, 2018;Silvestri et al, 2019). These works highlighted that the two analyzed AMF, R. irregularis and R. clarus, are equipped with a RNAi machinery characterized by 26-40 AGO-like, 3-21 RdRp, and 1-2 DCL proteins.…”
Section: The Comparative Analysis Of Fungal Rnai-related Proteins Revmentioning
confidence: 99%
See 1 more Smart Citation